Potential tuberculostatic agent: Micelle-forming pyrazinamide prodrug - Silva, M.; Ricelli, N. L.; El Seoud, O.; Valentim, C. S.; Ferreira, A. G.; Sato, D. N.; Leitel, CQF; Ferreira, E. I. (Wiley-Blackwell, 2006)
Pyrazinamide was condensed with the poly(ethylene glycol)-poly(aspartic acid) copolymer (PEG-PASP), a micelle-forming derivative was obtained that was characterized in terms of its critical micelle concentration (CMC) and micelle diameter. The CMC was found by observing the solubility of Sudan III in Poly(ethylene glycol)-poly(pyrazinamidomethyl aspartate) copolymer (PEG-PASP-PZA) solutions. The mean diameter of PEG-PASP-PZA micelles, obtained by analyzing the dynamic light-scattering data, was 78.2 nm. The PEG-PASP-PZA derivative, when assayed for anti-Mycobacterium activity, exhibited stronger activity than the simple drug.
Keywords: pyrazinamide; micelle-forming polymer; tuberculostatic prodrug